Applying the Behaviour Change Wheel to support deprescribing in long-term care: Qualitative interviews with stakeholder participants - Barbara Farrell; Jeremy Rousse-Grossman; Carmelina Santamaria; Lisa M. McCarthy (Elsevier, 2023)
Background: Implementation and behavioural science are increasingly being used to support development and translation of evidence-based interventions into practice. We used the Behaviour Change Wheel (BCW) approach in two stakeholder forums to identify target behaviours and supporting actions to inform the development of a framework to support deprescribing in long-term care homes. During our planning for these forums, we found many applications of the BCW approach used in healthcare. However, we found no accounts of stakeholders' experiences when the BCW approach was used with large groups of people who were mostly unfamiliar with behavioural science. Objective: The goal of this research was to gain insight into the use of the BCW approach in the context of developing a framework to support deprescribing in long-term care. Methods: This descriptive qualitative study employed one-on-one semi-structured interviews with Ontario long-term care stakeholders who had participated in one or both of two in-person forums that we hosted. Interviews were transcribed verbatim and an inductive content-analysis approach was used to code data and determine themes. Results: Fifteen interviews were conducted. Four themes were identified. First, the BCW was new and made sense, but people found it hard to identify target behaviours before planning solutions. Second, participants varied in their opinions as to whether the 'right' people were participating. Third, participants found that the forum activities, worksheets and facilitators helped people use the approach. Fourth, stakeholder perspectives about potential implementation challenges and strategies to maximize success were identified. Conclusions: Overall, participants were positive about the use of the BCW approach, however, its usefulness could be optimized by enhancing explanations, facilitation and logistics to ensure an initial focus on targeting behaviours. Making stakeholder perspectives transparent and ensuring mechanisms are present to ensure all views are sought and considered are also important to optimizing participant experience.